Prevalence of Suicidality in Major Depressive Disorder: A Systematic Review and Meta-Analysis of Comparative Studies - Cai, Hong; Xie, Xiao-Meng; Zhang, Qinge; Cui, Xiling; Lin, Jing-Xia; Sim, Kang; Ungvari, Gabor S.; Zhang, Ling; Xiang, Yu-Tao (Frontiers in Psychiatry, 2021)
Abstract Background: Suicidality is common in major depressive disorder (MDD), but there has been no review published about all aspects of suicidality. This meta-analysis and systematic review compared the prevalence of the whole range of suicidality comprising suicidal ideation (SI), suicide plan (SP), suicide attempt (SA), and completed suicide (CS), between patients with MDD and non-MDD controls. Method: Major international (PubMed, Embase and PsycINFO) and Chinese (Chinese Nation Knowledge Infrastructure and WANFANG) databases were systematically and independently searched from their inception until January 12, 2021. Results: Sixteen studies covering 85,768 patients (12,668 in the MDD group and 73,100 in the non-MDD group) were included in the analyses. Compared to non-MDD controls, the ORs for lifetime, past month, past year, and two-week prevalence of SI in MDD were 2.88 (95%CI 0.30-27.22; P=0.36), 49.88 (95%CI 2-8.63; P<0.001), 13.97 (95%CI 12.67-15.41; P<0.001) and 24.81 (95%CI 15.70-39.22; P<0.001), respectively. Compared to non-MDD controls, the OR for lifetime SP in MDD was 9.51 (95%CI 7.62-11.88; P<0.001). Compared to non-MDD controls, the random-effects ORs of lifetime and past year prevalence of SA was 3.45 (95%CI 1.58-7.52; P=0.002), and 7.34 (95%CI 2.14-25.16; P=0.002), respectively in MDD patients. No difference in the prevalence of CS between MDD and controls was found (OR 0.69, 95%CI 0.23-2.02; P=0.50). Conclusions: MDD patients are at a higher risk of suicidality, particularly SA, compared to non-MDD controls. Routine screening for a range of suicidality should be included in the management of MDD, followed by timely treatment for suicidal patients.